Beyond the Videos: A Narrative Inquiry Study of Student Engagement in a Flipped Classroom - Suningsih, Sri; Rohmatillah, Rohmatillah (Raden Intan State Islamic University of Lampung, Indonesia, 2025)
This study explores student engagement in a flipped classroom within the context of English as a Foreign Language (EFL) learning. Using a qualitative narrative inquiry approach, data were collected from semi-structured interviews and reflective journals of twenty undergraduate students at an Indonesian university. The analysis identified ten main themes: active participation, peer collaboration, teacher support, autonomy and control, emotional engagement, time management challenges, integration of technology, peer teaching, diversity of learning styles, and reflections on individual learning journeys. Findings show that the flipped classroom encouraged students to be more active, collaborate with peers, and take ownership of their learning. Teacher guidance and emotional connection also played a vital role in sustaining motivation. However, challenges such as time management and technological issues were reported. The study concludes that flipped classrooms can positively transform student engagement in EFL contexts when supported by proper guidance, technical resources, and strategies to address learning challenges.